Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.739988
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of the Zinc Homeostasis Network in Pseudomonas aeruginosa and Its Gene Expression Dynamics

Abstract: Zinc is one of the most important trace elements for life and its deficiency, like its excess, can be fatal. In the bacterial opportunistic pathogen Pseudomonas aeruginosa, Zn homeostasis is not only required for survival, but also for virulence and antibiotic resistance. Thus, the bacterium possesses multiple Zn import/export/storage systems. In this work, we determine the expression dynamics of the entire P. aeruginosa Zn homeostasis network at both transcript and protein levels. Precisely, we followed the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 63 publications
(115 reference statements)
4
28
0
Order By: Relevance
“…Analysis of DEGs revealed that NAC mainly acted as Zn 2+ chelator, inducing a strong Zn 2+ starvation response. DEGs associated with such response were consistent with data reported in previous studies addressing zinc homeostasis in P. aeruginosa and other bacteria ( Table 2 ) ( 17 22 ). In particular, 31 of the 46 upregulated DEGs belonged to the zur regulon and are known to be activated in response to Zn 2+ starvation ( Table 2 ) ( 17 22 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis of DEGs revealed that NAC mainly acted as Zn 2+ chelator, inducing a strong Zn 2+ starvation response. DEGs associated with such response were consistent with data reported in previous studies addressing zinc homeostasis in P. aeruginosa and other bacteria ( Table 2 ) ( 17 22 ). In particular, 31 of the 46 upregulated DEGs belonged to the zur regulon and are known to be activated in response to Zn 2+ starvation ( Table 2 ) ( 17 22 ).…”
Section: Resultssupporting
confidence: 90%
“…DEGs associated with such response were consistent with data reported in previous studies addressing zinc homeostasis in P. aeruginosa and other bacteria ( Table 2 ) ( 17 22 ). In particular, 31 of the 46 upregulated DEGs belonged to the zur regulon and are known to be activated in response to Zn 2+ starvation ( Table 2 ) ( 17 22 ). Such genes mainly included operons involved in zinc uptake (e.g., the PA4063-PA4064-PA4065-PA4066 operon, cntOLMI operon, and znuABC operon) and genes encoding zinc-independent paralogs of cellular proteins (i.e., type B 50S ribosomal proteins L31 and L36, RNA polymerase-binding protein DksA2, adn GTP-cyclohydrolase FolE2) ( Table 2 ) ( 17 23 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is vital for cells and must always be present in sufficient amounts, but can become toxic as soon as it exceeds a threshold (17). In the bacterium P. aeruginosa , eight zinc import and four zinc export systems have been described (4). In case of zinc excess, the Zur protein represses the expression of many import systems, thus preventing too much Zn from entering the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In the Gram-negative bacterium Pseudomonas aeruginosa , several systems are involved in Zn homeostasis (4,5). Zn import into the periplasm is mediated by TonB-dependent importers such as ZnuD.…”
Section: Introductionmentioning
confidence: 99%